2020
DOI: 10.22610/jevr.v10i2(v).2978
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Postgraduate Student Preferences for University Choice in Zambia: The Case of ZCAS University

Abstract: The aim of this study was to ascertain the university brand model that characterizes postgraduate student choice of ZCAS University. The brand model comprises brand attributes that attract postgraduate students to the university, the information sources they consult, who influences their decisions and what makes the university unique. The study was qualitative in design, while sampling of research participants was done purposively. Three focus group discussions involving seventeen first years part time and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
0
1
Order By: Relevance
“…Thus, the most influential factors of new university students' choice of study ranked from the quality of the university, relatively affordable tuition, accreditation, comfortable study rooms. Another study results revealed that student choice of university was influenced by quality of teaching, tuitions, availability of courses, facilities, and employability (Kayombo & Carter, 2016). However, the results of this study were in some points different from those of Amwila and Magdalena stating that the influential factors for university students' decision in choosing a university involve students' background of education, socialeconomic status of his/her parents, and campus facilities and infrastructures.…”
Section: Factor or Actor Influencing Student Choice Of Universitycontrasting
confidence: 74%
“…Thus, the most influential factors of new university students' choice of study ranked from the quality of the university, relatively affordable tuition, accreditation, comfortable study rooms. Another study results revealed that student choice of university was influenced by quality of teaching, tuitions, availability of courses, facilities, and employability (Kayombo & Carter, 2016). However, the results of this study were in some points different from those of Amwila and Magdalena stating that the influential factors for university students' decision in choosing a university involve students' background of education, socialeconomic status of his/her parents, and campus facilities and infrastructures.…”
Section: Factor or Actor Influencing Student Choice Of Universitycontrasting
confidence: 74%
“…Location can be a consideration for private HEIs to separate themselves from their competitors, influencing students' decisions (Kayombo et al, 2020). Compared to other institutions, the uniqueness of https://doi.org/10.…”
Section: Locationmentioning
confidence: 99%
“…Supported by (Kayombo et al, 2020;Mustafa et al, 2018;Yusuf et al, 2017), location is the most reliable factor affecting students' decision to attend a specific institution. Fifth, employment opportunities directly affect students' choice to enrol in a private HEI.…”
Section: Significantmentioning
confidence: 99%
See 1 more Smart Citation